Evaluation of Lord’s Anal Dilatation for Incontinence & Recurrence in the Management of Anal Fissure - Haider Kamran, Enas Nawaz Khan, Muhammad Ibrahim Shuja, Muhammad Tasleem, Uzma Shabbir, Valeeja Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fissure-in-Ano is a commonly seen entity in surgical practice. Various approaches had been adapted since ages for its management including both conservative & surgical. Amongst the surgical approaches Lord’s Anal Dilatation (LAD) is a modality long been practiced to manage patients not responding to conservative treatment & those with chronic anal fissure. Recent trend is towards preferential practice of Lateral Internal Sphincterotomy (LIS) in the management of anal fissure. Pleaders of LIS are critical as well to the approach of LAD, although LAD in many clinical setups is still a widely practiced & viable option, especially in third world countries. Objective of conducting this study is to evaluate the LAD in our hospital setup for its much debated complications of incontinence and recurrence. Methods: This descriptive study was designed & carried out at the surgical units of Ayub Teaching Hospital Abbottabad from November 01, 2012 to May 31, 2017. A total of 129 patients with acute anal fissure (not responding to conservative measures, being in agony) & chronic anal fissure (duration longer than 06 weeks) were included in study after taking informed consent. Patients were managed with LAD & later followed for 01 year for the evidence of permanent flatus / faecal incontinence & fissure recurrence. Results: Out of the 129 patients included in study we had successfully been able to follow 102 patients for one year, while 27 patients were lost at various stages of follow-up and thus dropped off the final stage of study (i.e. calculation of incontinence & recurrence rate). Post-operative pain intensity & early mobility factor was found much better in this study. 23 patients initially complaining of flatus incontinence for 02–09 days were settled with pelvic floor exercises while none was found with an early or late complication of faecal incontinence. Similarly follow-up for 01 year period revealed none with recurrence issue. Conclusion: LAD in our study proved a safe & effective approach in the management of patients with anal fissure un-responsive to conservative measures, having no permanent incontinence or recurrence issues & may therefore be safely practiced in our setup like LIS procedure. Keywords: Anal fissure, Lord’s anal dilatation, lateral internal sphincterotomy, incontinence, recurrence